Nonlinear absorption in interacting Rydberg electromagnetically-induced-transparency spectra on two-photon resonance - Tebben, Annika; Hainaut, Clément; Salzinger, Andre; Geier, Sebastian; Franz, Titus; Pohl, Thomas; Gärttner, Martin; Zürn, Gerhard; Weidemüller, Matthias (Physical review, 2021)
We experimentally investigate the nonlinear transmission spectrum of coherent light fields propagating through a Rydberg EIT medium with strong atomic interactions. In contrast to previous investigations, which have largely focused on resonant control fields, we explore here the full two-dimensional spectral response of the Rydberg gas. Our measurements confirm previously observed spectral features for a vanishing control-field detuning, but also reveal significant differences on two-photon resonance. In particular, we find qualitative deficiencies of mean-field models and rate-equation simulations as well as a third-order nonlinear susceptibility that accounts for pairwise interaction effects at low probe-field intensities in describing the nonlinear probe-field response under EIT conditions. Our results suggest that a more complete understanding of Rydberg EIT and emerging photon interactions requires to go beyond existing simplified models as well as few-photon theories.
Gesehen am 15.07.2021